The Demand Model of the Danish National Model - Rich, Jeppe (Proceedings from the Annual Transport Conference at Aalborg University, 2010)
In the present paper the structure of the demand model framework for the new Danish national model is outlined. It involves a discussion at two levels. At the framework level, we discuss how demand is modelled in a number of parallel sub-models and how these are linked. An issue is to represent all transport but on the other hand avoid double counting. At the sub-model level, special attention is given to the week-day model as well as the international component of the model. The model for week-day traffic represents the most important components with respect to overall mileage and congestion and is therefore particularly important from a policy point of view. The international models are relevant because these are central to the Fehmarn Belt application of the model to be finished in the first quarter of 2012. For the international models we consider segmentation and nesting structure for the international day model, the transit model, and the overnight model. Finally, we discuss how trip chains of higher dimensions can be represented in a matrix form applicable for the assignment procedure.